Penerapan Smart Village di Desa Melung Kecamatan Kedungbanteng Kabupaten Banyumas (Analisis Penerapan Smart Governance, Smart People, Smart Economy di Desa Melung Kecamatan Kedungbanteng, Kabupaten Banyumas) - Rahayu, Sinta Puspa (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2022)
Smart City is a concept that is considered to have succeeded in overcoming various problems in cities which can then be adopted to be developed in a smaller context, namely in the Village or known as Smart Village. The Smart concept in this study uses the Cohen concept. There are several dimensions to the Smart City/Smart Village Cohen concept, including Smart Governance, Smart People, Smart Economy, Smart Environment, Smart Living The purpose of this study is to describe the application of smart villages and analyze the concept of smart villages in helping the Melung Village in developing village potential. The research method used is descriptive qualitative through interviews, observations and documentation of informants. The informants in this study were the Melung village government, the community and community group leaders and other related external parties. The result of the research is that the Melung village government has been very good at disclosing public information, at the end of every year even the budget used by the village can be seen by the community around the village government office. This openness will foster public confidence in the performance of village officials who manage village funds. With the government always being open to managing funds and other programs, this shows that the smart village has been implemented. Keywords: Smart Economy, Smart Governance, Smart People, Smart Village